Aktualisasi nilai-nilai Pancasila sebagai fondasi pendidikan hak asasi manusia bagi generasi muda - rohman, m. taufiqur (Maliki Interdisciplinary Journal, 2026)
Human Rights (HAM) violations remain a major challenge that hinders social justice and harms the nation’s dignity. Efforts to enforce human rights cannot rely solely on legal regulations but require the support of moral education and character building from an early age. This study aims to examine the vital role of Pancasila values as a philosophical foundation in the development of human rights education for the younger generation. This study applies a qualitative descriptive method with a literature approach, exploring data from various scientific journals and related academic references. The findings show that the five precepts of Pancasila contain distinct universal human rights principles, such as recognition of human dignity, justice, and equality. Integrating these noble values into the education curriculum and social life is a strategic step to produce a future generation that is humanist, tolerant, and committed to protecting the rights of others.